Nowo odkryty relief wotywny z Ptolemais (Libia) - Mikocki, Tomasz; Muszyńska -Mikocka, Monika (Acta Universitatis Lodziensis. Folia Archaeologica, 2009)
During the archaeological excavations conducted by the Institute of Archaeology of the Warsaw University in Ptolemais (Libya) a very well preserved votive relief was discovered. The relief displays an iconography typical for this group of objects. The main figure – although not the founder of the ex-voto – is a hero depicted mounting an upraised horse. Before him a young man, unproportionally smaller, is shown running. Facing the two male figures stands a veiled woman holding in her hand a sacrifice vessel. As has been proven in the case of several other similar, locally produced objects, the running figure portrays the founder of the relief – a young boy taking part in some gymnastic activity. The chronology of the object can only be established basing on stylistic elements – the archaeological context is not an indicator as the relief was found in a destruction layer dated to the mid Roman period and must have been displayed by the owner of the villa as an object of art or of a cult. The analysis of the facial features and hairstyle of the hero – the most distinctive elements of the represented elements – in reference to numismatic portraiture seem to point to a Hellenistic date – perhaps IIIrd c. B.C. The article also presents several analogous, previously published or unpublished reliefs produced locally in Cirenaica.